PELATIHAN PENULISAN KREATIF ENGLISH POETRY BERBASIS NILAI-NILAI KEISLAMAN DI MAN SUKOHARJO - Wijaya, Rahmaditya Khadifa Abdul Rozzaq; Wardhani, Evi Murti; Kamaluddin, Ahnaf Dzaky; Bataiv, Misbah Faturrahman (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2024)
This community service aims to improve students' creative writing skills in English and integrate Islamic values in their literary works. Through this training, students are expected to develop creative poetry writing skills while instilling a deeper understanding of Islamic values such as honesty, simplicity, and respect. The implementation method involved several stages starting with preparation and planning that included needs identification, curriculum development, and recruitment of experienced resource persons. The training consisted of theory, practice, and mentoring sessions designed to provide in-depth understanding and personalized guidance for students. Theory sessions cover creative writing techniques and poetry structure, while practical sessions provide opportunities for students to apply their knowledge through writing exercises and group discussions. Mentoring sessions provide specialized assistance to help students improve the quality of their work. Evaluation is conducted through work assessment and feedback from participants, which will be used to improve future programs. The outcome of the training is expected to be the improvement of students' creative writing skills, the publication of a poetry anthology, and the establishment of a literary club for the sustainability of the program. Collaboration with schools, literary communities, and local religious institutions is also conducted to support the implementation and sustainability of this program. With a structured and comprehensive implementation, this program is expected to have a significant positive impact on MAN Sukoharjo students in developing creative writing skills and understanding and applying Islamic values in their lives.